ANALISIS PENGGUNAAN MEDIA SOSIAL TERHADAP PRESTASI BELAJAR GENERASI ALPHA DI SEKOLAH DASAR - Amalia Hasanah; Fatma Agustriana; Ghina Yusnita; Yusniarti Yusniarti; Ali Rachman (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2025)
This research aims to understand the impact of social media on students' performance, as social media is currently evolving rapidly in line with the times. The most commonly used social media platforms today are WhatsApp, Instagram, TikTok, and Facebook. Social media has a significant influence on people, especially students, in terms of communication, socialization, and acquiring more knowledge. Social media can also serve as a means for creative development. However, the use of social media has both negative and positive impacts on students, depending on how they utilize it. This is where the role of parents and teachers becomes crucial, so that students can set limits on their social media use to avoid negative consequences